80 Effects of macronutrient composition of milk replacer on body composition and intestinal development in neonatal dairy calves. (5th December 2019) - Welboren, Anna C; Hatew, Bayissa; Leal, Leonel; Martin-Tereso, Javier; Steele, Michael A
Abstract: Most milk replacers (MR) contain a higher lactose:fat ratio compared to whole milk, potentially affecting nutrient absorption and use by the calf. This study evaluated how body composition and intestinal development were affected when lactose was replaced with fat in MR. Thirty-four calves (43.3 ± 0.8 kg) were blocked (BW and dam parity), and randomly assigned to a high-lactose (43.8% lactose and 17.1% crude fat) or high-fat (37.9% lactose and 23.4% crude fat) MR. Calves were fed pooled colostrum within 2 h (18% of metabolic body weight (MBW)) and 12 h (9 %MBW) postnatal, followed by MR feeding (18 %MBW) twice daily. Calves were weighed pre-prandially at birth and on d 7. Calves were euthanized on d 7 to sample intestinal tissue and analyze body composition using dual-energy x-ray absorptiometry. Samples of intestinal segments were processed to evaluate histomorphology using bright-field microscopy. Data were analyzed using PROC MIXED in SAS software. Total gain (3.90 vs. 2.29 ± 0.38 kg, P = 0.01) and gain:ME intake (44.64 vs. 28.61 ± 4.32 kg, P = 0.02) were greater for high-fat compared to high-lactose calves, whereas body composition was unaffected (P = 0.13). Proportionally, the large intestine was 0.11 ± 0.02 %BW heavier (P = 0.03) in high-fat calves compared to high-lactose calves, while their small intestine tended to be 0.16 ± 0.06 %BW heavier (P = 0.09). Small and large intestine length did not differ (P = 0.96). High-fat calves had wider villi (125.41 vs. 96.58 µm, P = 0.05) in the jejunum but shorter villi (414.17 vs. 470.96 µm, P = 0.02) in the ileum compared to high-lactose calves. Macronutrient composition affected intestinal histomorphology and improved efficiency of ME use for BW gain. Understanding how fat (including its source) influences nutrient efficiency in dairy calves may improve nutritional strategies on farm.